Fase-fase Pembangunan Keraton Surosowan-Banten Lama - Permana, R. Cecep Eka (Wacana, Journal of the Humanities of Indonesia, 2004)
The Sorosuwan Palace played a major role for the kingdom of Banten in the period between the 16th century and the 19th century. In such a long period of time, the Sorosuwan Palace experienced ups and downs in its development. Based on a library research, it is known that the Sorosuwan Palace was renovated several times. This is most clearly seen in the differences found in the representations of the Sorosuwan Palace in the maps of Banten of 1596, of 1624 and of 1726. Outstanding changes can especially be seen in the maps of 1739, 1825, and 1900. The last three maps represent the Sorosuwan Palace as oblong in form with a bastion in each corner (which is similar to the present representation of the Keraton), while in the previous maps it is represented as a building with steps where it protrudes at the top, surrounded by other buildings. Field study reveals no indication that there had been two phases in the process of its building. This can be gathered from the remnants of the structure of the building in several places indicating that there had been a two-layered floor structure and an overlapped structure.